Pengembangan E-Modul Praktikum Fisika Dasar 1 dengan Pendekatan STEM untuk Menumbuhkan Kemandirian Belajar dalam Pembelajaran Daring - Desy Kumala Sari (Universitas Sebelas Maret, 2021)
The experiment activities of fundamental physics in the laboratory become challenging during Covid 19 Pandemic. The experiment should be carried out remotely, and there is a need to develop an electronic practicum module containing an interactive tutorial video. The research aims to create an electronic module of Fundamental Physics I Experiment with STEM (Science, Technology, Engineering, and Mathematics) Approach. The used development model was 4D (Define, Design, Develop, and Disseminate). The collected data instruments are expert validation questionnaire, practicality questionnaire, and independence questionnaire to determine the product effectivity. Ideal Standard Deviation analysed data to comprehend its category. The interpreted result showed the product feasible, practices, and effective to use in the learning process. The average feasibility score is 71, and the practicality aspect has a score of 38. Both of them have excellent criteria. Besides that, the developed product also improves students’ autonomy in experimental activities.